Core-resonance line-shape analysis of atoms undergoing strong-field ionization. (21st December 2022) - Hartmann, M; Hutcheson, L; Borisova, G D; Birk, P; Hu, S; Brown, A C; van der Hart, H W; Ott, C; Pfeifer, T
Abstract: Using attosecond transient absorption spectroscopy for time delays where the near-infrared pump and the extreme ultraviolet (XUV) probe pulses overlap, sub-cycle structures in the build-up of absorption lines in xenon ions are investigated as a function of the pump intensity during strong-field ionization. We observe a half-cycle-periodic change in the line-shape asymmetry of the ionic 4d–5p resonances. Analyzing the line shapes, we find that in particular the phase of the induced dipole emission is modified, and the magnitude of this phase modulation decreases with increasing laser intensity. We discuss the influence of ground state depletion on interfering pathways involved in XUV-assisted strong-field ionization.